Autologous cord blood harvesting in North Eastern Italy: ethical questions and emerging hopes for curing diabetes and celiac disease. - Parco, Sergio; Vascotto, Fulvia (Int J Gen Med, 2012)
BACKGROUND: The Friuli Venezia Giulia (FVG), a region of North Eastern Italy, has passed legislation (Decree No 2324/2010) to regulate the banking of umbilical cord blood samples for personal, autologous, or family-directed use, and to implement the Agreement of the State-Regions Permanent Conference (Decree No 62/CSR/2010). This paper aims to identify the formalities and the reasons why families collect and bank their cord blood in foreign banks for both personal and private use. METHODS: To this end, at the Institute for Maternal and Child Health of Trieste (the regional capital city of the FVG), Italy, which assists about 1800 pregnant women a year, 129 questionnaires, drafted from January 2010 to December 2011 and concerning the granting of authorization to export samples, were examined. RESULTS: The collected data showed that 75% of involved families had resorted to anonymous public collection, which is available to anyone with therapeutic needs, and provided compatibility and hematologic protocols recognized by the scientific and international community (main indications: leukemia, hemoglobinopaties, and inherited hematologic and immunologic disorders). Conversely, 25.0% requested private storage at a foreign bank for personal or family-dedicated use. The principal motivation by disease was for treatment for diabetes (22.4%) and celiac disease (19.7%) (a multiorgan disease for which the FVG region has provided safeguards by approving a specific law granting support to families; Decree No 561/2007). For these two types of disease we found that information was received from the internet and not from general medical physicians, with a significant difference found using the χ(2) test (P < 0.01). CONCLUSION: The indication of treating these diseases with cord blood stem cell transplantation appears to be well grounded and encouraging, and has recently been corroborated by the international literature; however, the economic and social motivations promoting cord blood storage, for a fee, in the event of diseases that are still under study, require accurate information through general medical physicians on the actual possibilities of treatment.